Frictorq, accessing fabric friction with a novel fabric surface tester - Lima, Mário (2005)
A new method to characterise the coefficient of friction of textile fabrics is proposed. The principle is based on the dry clutch, where an annular shaped flat upper body that is kept still, rubs against a lower flat surface, which rotates around a vertical axis at a constant angular velocity. Friction coefficient between the two contacting surfaces is then proportional to the level of the dragging torque between them, measured by means of a precision reaction torque sensor. Contact pressure is constant, given by the own weight of the upper body. The signal from the torque sensor is digitalised through an electronic interface and fed into a PC where friction coefficient is worked out. Finally, experimental work is reported.